Full factorial design of the effects of coagulants and processing variables on the physicochemical quality and texture profile analysis of kenaf seed tofu - Ibrahim, Shafa’atu Giwa; Karim, Roselina (Open Exploration Publishing Inc, 2024)
Kenaf (Hibiscus cannabinus) is an herbaceous plant of economic significance, the seed is rich in essential nutrients and has the potential for the production of protein-based products. This study investigated the holistic effects of coagulants, kenaf seed-to-water ratio for extraction, and temperature of addition of coagulant on the physicochemical and texture quality of kenaf seed tofu. Randomised full factorial design was used to obtain different formulations of kenaf seed tofu production under 4 factors at different levels. The main factors of coagulant types, seed-to-water ratio and temperature of addition of coagulant significantly affected the yield, pH, crude protein, crude fat, lightness, yellowness and cohesiveness of the kenaf seed tofu while the redness of the tofu was significantly affected by the coagulant types only. However, the hardness, chewiness and springiness of the tofu were affected by coagulant types and concentrations. Additionally, the 2-way interactions significantly affected the texture profile of the tofu. Though, the 3-way and 4-way interactions have no significant effect on the texture characteristics of the kenaf seed tofu. The tofu made with aluminium potassium salt at concentrations of 0.50 g/100 mL and 1.00 g/100 mL, and 80°C temperature of addition of coagulant formed the highest yield of 71.22 g/100 g and 77.57 g/100 g, respectively. This study also found that aluminium potassium salt and glucono-delta-lactone, with the use of 1:3 seed-to-water ratio and 70°C or 80°C temperature of addition of coagulant were better in terms of hardness and chewiness.